The Role of Depression in Bridging Resilience and General Decision-Making Style (GDMS) in Emerging Adults - Maya Rahadian Septiningtyas; Lobby Loekmono (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
Emerging adult students face complex adaptation challenges that demand effective decision-making abilities. This study aims to examine the mediating role of depression in the relationship between resilience and decision-making styles. Using a quantitative correlational design, data were collected from 70 college students through purposive sampling. The instruments employed included the Connor-Davidson Resilience Scale (CD-RISC), the Beck Depression Inventory-II (BDI-II), and the General Decision-Making Style (GDMS) inventory. Mediation analysis using the PROCESS Macro Model 4 revealed that resilience was negatively correlated with depression (r = -0.612) and positively correlated with decision-making style (r = 0.559). The mediation test confirmed that depression serves as a partial mediator (indirect effect 0.419;95% CI [0.267, 0.570]). These findings underscore that resilience enhances decision-making quality both directly and indirectly by reducing depressive symptoms